Production and Purification of Pectinase by Soil Isolate Penicillium Sp and Search for Better Agro-Residue for its SSF - Chaudhari2*, Nitinkumar P. Patil1; Bhushan L. (Recent Research in Science and Technology, 2010)
Pectinase producing microorganisms were isolated from pectin industry waste using selective isolation technique. Among them, a potential culture was identified on morphological basis as Penicillium sp. It was found to produce significant amount of extracellular pectinase under submerged fermentation process. The type of enzyme produced was subsequently identified as polygalacturonase (PG). On partial optimization, culture showed maximum enzyme production at 35 oC in a medium having pH 6.0 containing 1.5% pectin on 72 h of incubation. The PG produced by the isolate was further purified by ammonium sulphate precipitation, size exclusion and ion exchange chromatography. The molecular weight of purified enzyme was determined to be 35 kDa by SDS-PAGE. Under optimized conditions, purified PG showed 98.66 U/ml activity which was almost 12 fold higher than crude. In view of cost effective pectinase production, substrate optimization using solid state fermentation was carried out amongst which orange bagasse gave 64.50 U/gm PG activity which was higher than other natural substrates.